THE IMPACT OF CORRECTIVE AND PREVENTIVE MEASURES ON THE PHYSICAL FITNESS OF WOMEN IN EARLY ADULTHOOD WITH VARIOUS POSTURAL BIOMECHANICAL PROFILES - Samoiliuk, O. V.; Grygus, I. M.; Bychuk, O. I. (Rehabilitation and Recreation, 2025)
Introduction. The concept of health-oriented physical activity views health as a multifactorial state determined by the conscious adoption of preventive strategies. Physical activity is a key, and often dominant, determinant that provides a modulating effect on physiological systems, enhancing the body’s resistance to external and internal stressors.The study aimed to determine the characteristics of physical fitness in women of the first mature age period with different types and levels of biomechanical postural profiles after the implementation of corrective and preventive measures.Methods. The research methods included theoretical analysis and synthesis of literature sources, photographic analysis of posture, pedagogical experiment, and mathematical statistics.Results. Functional movement screening is an effective method for assessing physical fitness and motor skills, widely used for the biomechanical monitoring of various population groups. Its application simplifies the monitoring process, improving supervision over participants in corrective and preventive programs through simple calculations, objective scoring, and informative conclusions. The development of corrective and preventive measures for women of the first mature age period with various musculoskeletal biomechanics disorders was based on an original concept that accounted for global, socio-pedagogical, personal, and biological prerequisites. A total of 36 women aged 25–34 participated in the study. The experimental data confirmed the positive effect of these measures on flexibility in women aged 30–34 with a rounded back. The changes in scores significantly exceeded the set goal, indicating the high effectiveness of the corrective and preventive measures in this aspect. However, the goal of improving strength indicators was not achieved, as no statistically significant changes were recorded in the corresponding tests. This points to the need for further adaptation of the corrective programs for more effective development of muscle strength.Conclusions. Summarizing the results of the experiment aimed at testing corrective and preventive measures on the physical fitness of women with different posture types and biomechanical profile levels, an increase in the average scores for physical fitness tests was recorded, with a significant portion of participants meeting or exceeding the set goals. This evidence proves that the proposed original concept and its practical implementation effectively improved the biomechanics of women’s body spatial organization.